Personalized treatment planning for heart interventions using tissue-mimicking 3D printing. Issue 2 (30th April 2018) - Qian, Zhen; Vannan, Mani A
Percutaneous valve treatment has been frequently targeted for 3D printing-guided preprocedural planning. In a recent study, we have developed a novel treatment planning platform using sensor-enabled tissue-mimicking 3D printing to quantitatively predict the occurrence, severity and location of paravalvular leak after transcatheter aortic valve replacement. This platform consisted of two major components: a novel tissue-mimicking 3D printing technique and an in vitro imaging-based strain quantification technique. We have demonstrated the feasibility of manufacturing, such a phantom to provide not only an accurate anatomic model but also a benchtop testing platform that gives important pathophysiologic information regarding the cardiac intervention. As cardiovascular medicine is shifting more toward personalized treatment, 3D printing will play a more important role in patient-specific planning for heart procedures.